2006
DOI: 10.1093/jxb/erj198
|View full text |Cite
|
Sign up to set email alerts
|

The role of ascorbic acid in the control of flowering time and the onset of senescence

Abstract: Ascorbic acid (AA) is not only an important antioxidant, it also appears to link flowering time, developmental senescence, programmed cell death, and responses to pathogens through a complex signal transduction network. The biological activity of AA is defined by its oxidation and subsequent regeneration into the reduced form. Some studies suggest that the total endogenous level of AA influences induction of flowering and senescence. Both processes require the co-ordinated regulation of gene expression, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
174
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(182 citation statements)
references
References 66 publications
3
174
1
4
Order By: Relevance
“…Ascorbic acid is an essential compound for plant tissues since it has antioxidant functions, and acts as co-enzyme in an enzymatic cofactor and plant growth regulator [14]. It has synergistic effect on improving growth, flowering, yield and fruit quality of fruit crops [15], [16] , [17] and [18]. [19] reported that marked in vivid coloures.…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid is an essential compound for plant tissues since it has antioxidant functions, and acts as co-enzyme in an enzymatic cofactor and plant growth regulator [14]. It has synergistic effect on improving growth, flowering, yield and fruit quality of fruit crops [15], [16] , [17] and [18]. [19] reported that marked in vivid coloures.…”
Section: Introductionmentioning
confidence: 99%
“…However, Raper et al (1988) and Rideout et al (1992) hypothesized that floral transition is stimulated by an imbalance in the relative availability of carbohydrate and nitrogen in the shoot apical meristem. Barth et al (2006) suggest that the flowering phenotype is likely linked to the endogenous ascorbic acid content. Degradation and removal of flowering repressor(s) by ectopic SPAE expression in transgenic Arabidopsis plants provides another possibility.…”
Section: Expression Of Sweet Potato Asparaginyl Endopeptidase Spae Almentioning
confidence: 99%
“…The reasons and mechanisms are not clear. However, an imbalance in the relative availability of carbohydrate and nitrogen in the shoot apical meristem (Raper et al, 1988;Rideout et al, 1992), the change of endogenous ascorbic acid content (Barth et al, 2006), and possible nonspecific degradation and removal of flowering repressor(s) by ectopic SPCP2 expression are suggested.…”
Section: Expression Of Sweet Potato Papain-like Cysteine Protease Spcmentioning
confidence: 99%
“…Ascorbic acid (vitamin C) has a regulatory role in promoting productivity in many plants, Ascorbic acid acts as a cofactor for several enzymes and regulates the phytohormone-mediating signaling processes [19] and many physiological processes in plants [20,21]. Ascorbic acid is cofactors for enzyme activity, and effects on plant antioxidation capacity, heavy metal evacuation and detoxification and stress defense [22].…”
Section: Introductionmentioning
confidence: 99%